2024
DOI: 10.3390/biology13010030
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Non-Apoptotic Sperm Selected by Magnetic Activated Cell Sorting (MACS) to Enhance Reproductive Outcomes: What the Evidence Says

Nicolás Garrido,
María Gil Juliá

Abstract: Sperm selection of the most competent sperm is a promising way to enhance reproductive outcomes. Apoptosis is the programmed cell death process to maintain tissue homeostasis, and MACS sperm selection of non-apoptotic cells enables the removal of apoptotic sperm from an ejaculate, thus leaving the non-apoptotic available to be microinjected, but given the associated costs of adding these sperm selection steps to the routine practice, there is a need for a careful examination of the literature available to answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…3 of 13 ICSI failures/miscarriages with an unknown female cause with higher DNA-fragmentation by the male partner, though its application lacks any high level evidence, therefore its application should be consulted individually with each couple [22]. Since the quality of the current evidence is very low, the true clinical effects of the method on ART outcomes are still a debate and large randomized controlled studies are missing.…”
Section: X For Peer Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…3 of 13 ICSI failures/miscarriages with an unknown female cause with higher DNA-fragmentation by the male partner, though its application lacks any high level evidence, therefore its application should be consulted individually with each couple [22]. Since the quality of the current evidence is very low, the true clinical effects of the method on ART outcomes are still a debate and large randomized controlled studies are missing.…”
Section: X For Peer Reviewmentioning
confidence: 99%
“…One of the latter is the externalisation of phosphatidylserine (PS), which is a phospholipid located normally on the inner surface of the cell membrane [21]. Unfortunately, spermatozoa can carry this and other early signs of apoptosis without significant impact on morphology or motility, thus it can escape further phases of programmed cell death and fertilise the oocyte [22]. In a study by Hichri et al showed that distinct apoptotic alterations (the ratio of activated caspases, externalized PS, DNA-fragmentation) are reliable predictors of ART outcomes independently of conventional sperm parameters, DNA-fragmentation with best predictive value [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation